I'm trying to calculate an integral over the generalized Poincare upper half plane, then I find that I need to show the following identity:

Let $X=(X_{i,j})\in\mathrm{GL}(n,\mathbb R)(n\geq 3)$ and $r$ be a positive integer such that $2\leq r\leq n-1$. For any $1\leq \ell_1<\ell_2<\cdots< \ell_r\leq n$, we define \begin{eqnarray*} \det(\ell_1,\ell_2,\cdots,\ell_r):=\det\left\{ \left( \begin{array}{cccc} X_{n-r+1,\ell_1} & X_{n-r+1,\ell_2} & \cdots & X_{n-r+1,\ell_r} \\ X_{n-r+2,\ell_1} & X_{n-r+2,\ell_2} & \cdots & X_{n-r+2,\ell_r} \\ \vdots & \vdots & \cdots & \vdots \\ X_{n,\ell_1} & X_{n,\ell_2} & \cdots & X_{n,\ell_r} \\ \end{array} \right)\right\}. \end{eqnarray*} Let \begin{eqnarray*} A&=&\left(\sum\limits_{1\leq \ell_1<\cdots<\ell_{r-1}\leq n-1}[\det(\ell_1,\cdots,\ell_{r-1})]^2\right)\times\left(\sum\limits_{1\leq \ell_1<\cdots<\ell_{r-1}\leq n-1}[\det(\ell_1,\cdots,\ell_{r-1},n)]^2\right)\\ B&=&\left(\sum\limits_{1\leq \ell_1<\cdots<\ell_{r}\leq n-1}[\det(\ell_1,\cdots,\ell_{r})]^2\right)\cdot\left(\sum\limits_{1\leq \ell_1<\cdots<\ell_{r-2}\leq n-1}[\det(\ell_1,\cdots,\ell_{r-2},n)]^2\right)\\ C&=& \left(\sum\limits_{1\leq \ell_1<\cdots<\ell_{r-1}\leq n-1}\det(\ell_1,\cdots,\ell_{r-1})\cdot \det(\ell_1,\cdots,\ell_{r-1},n)\right)^2. \end{eqnarray*} Show that $A-B=C$.

The cases $n=3,4$ can be verified by Mathematical.

The case $r=2$ with any $n\geq 3$ can be verified easily by a direct calculation, but how to prove this identity for general $r$ ? Any comments and suggestions are welcomed!

  • $\begingroup$ this seems to be a moment problem in disguise? $\endgroup$
    – Suvrit
    Nov 9, 2013 at 14:49
  • 1
    $\begingroup$ I've seen some determinant identities that I'd classify as "lost to time" ... you could track down references 11 and 14 in math.ubc.ca/~gerg/papers/downloads/AAIMHNIE.pdf and scan through them for inspiration. $\endgroup$ Nov 9, 2013 at 21:02
  • $\begingroup$ what does det$(l_1,..,l_k,n)$ mean? the question is about the last $n$, a number. $\endgroup$
    – username
    Nov 11, 2013 at 14:41
  • 1
    $\begingroup$ All the $\ell_j$ are numbers too.... $\det(\ell_1,\dots,\ell_k,n)$ means the same thing as $\det(\ell_1,\dots,\ell_k,\ell_{k+1})$ where $\ell_{k+1}$ happens to equal $n$. $\endgroup$ Nov 11, 2013 at 17:59
  • 1
    $\begingroup$ My friend Yeping ZHANG had already proved this result last night using Wedge product. I will email to you latter. Thank you very much for the answers. $\endgroup$
    – Enlin Yang
    Nov 12, 2013 at 1:00

1 Answer 1


The following proof is due to Yeping ZHANG:

Let $V$ be a $n$ dimensional Euclidean vector space. Let $(e_1,\cdots,e_n)$ be an orthogonal basis.

For any $k=1,\cdots,n$, let $\Lambda^k V$ the $k$-th exterior product of $V$. We equip $\Lambda^k V$ with a metric ${\lVert \cdot \rVert}_{\Lambda^k V}$ such that $(e_{l_1}\wedge\cdots\wedge e_{l_k})_{1\leq l_1 < \cdots < l_k\leq n}$ is an orthogonal basis. Let ${\langle \cdot,\cdot \rangle}_{\Lambda^k V}$ be the associated inner product.

Let $v_1,\cdots,v_k\in V$, whose coodinates with respect to $(e_1,\cdots,e_n)$ are given by \begin{equation} v_i = \sum_{j=1}^n t_{ij}e_j \;, \end{equation} where $i = 1,\cdots,k$. Let $T=(t_{ij})_{1\leq i \leq k, 1\leq j \leq n}$ be the associated matrix. For $1\leq l_1 < \cdots < l_k\leq n$, set $T(l_1,\cdots,l_k)=(t_{ij})_{1\leq i \leq k, j = l_1,\cdots l_k}$. Then \begin{equation} v_1 \wedge\cdots\wedge v_k = \sum_{1\leq l_1 < \cdots < l_k\leq n} \, \det \, T(l_1,\cdots,l_k) \, e_{l_1}\wedge\cdots\wedge e_{l_k} \;, \end{equation} in particular \begin{equation} {\lVert v_1 \wedge\cdots\wedge v_k \rVert}_{\Lambda^k V}^2 = \sum_{1\leq l_1 < \cdots < l_k\leq n} [ \, \det \, T(l_1,\cdots,l_k) \, ]^2 \;. \end{equation}

With the above observation, we can interpret the question as the follows.

Set \begin{equation} x_i = \sum_{j=1}^n X_{ij}e_j \;, \end{equation} where $i=1,\cdots,n$. Let \begin{align} x_{n-r+2} \wedge\cdots\wedge x_n = \alpha + \beta \wedge e_n \;,\nonumber\\ x_{n-r+1} \wedge\cdots\wedge x_n = \gamma + \delta \wedge e_n \;, \end{align} with $\alpha,\beta,\gamma,\delta$ generated by $e_1,\cdots,e_{n-1}$. We have \begin{align} A & = {\lVert \alpha \rVert}_{\Lambda^{r-1} V}^2 \cdot {\lVert \delta \rVert}_{\Lambda^{r-1} V}^2 \;,\nonumber\\ B & = {\lVert \gamma \rVert}_{\Lambda^r V}^2 \cdot {\lVert \beta \rVert}_{\Lambda^{r-2} V}^2 \;,\nonumber\\ C & = {\langle \alpha , \delta \rangle}_{\Lambda^{r-1} V}^2\;. \end{align}

We have \begin{equation} x_i = y_i + X_{i,n}e_n \;, \end{equation} where $y_i = X_{i,1}e_1 + \cdots X_{i,n-1}e_{n-1}$. Then \begin{align} \alpha & = y_{n-r+2}\wedge\cdots\wedge y_n \;,\nonumber\\ \beta & = \sum_{l=n-r+2}^n (-1)^{n-l} X_{l,n} y_{n-r+2}\wedge\cdots\wedge y_{l-1}\wedge y_{l+1}\wedge\cdots\wedge y_n \;,\nonumber\\ \gamma & = y_{n-r+1}\wedge\cdots\wedge y_n \;,\nonumber\\ \delta & = \sum_{l=n-r+1}^n (-1)^{n-l} X_{l,n} y_{n-r+1}\wedge\cdots\wedge y_{l-1}\wedge y_{l+1}\wedge\cdots\wedge y_n \;. \end{align}

Case $1$. If one of $y_{n-r+2},\cdots,y_n$ is zero, we have \begin{equation} \alpha = \gamma = 0 \;, \end{equation} trivially, we get $A=B+C$.

Case 2. If $y_{n-r+1}=0$, we have \begin{align} \gamma & = 0 \;,\nonumber\\ \delta & = (-1)^{r-1}X_{n-r+1,n}\alpha \;. \end{align} Thus \begin{align} A & = X_{n-r+1,n}^2 {\lVert \alpha \rVert}_{\Lambda^{r-1} V}^4 \;,\nonumber\\ B & = 0 \;,\nonumber\\ C & = X_{n-r+1,n}^2 {\lVert \alpha \rVert}_{\Lambda^{r-1} V}^4 \;. \end{align} We find $A=B+C$.

Case 3. We suppose that none of $y_{n-r+1},\cdots,y_n$ is zero.

Without changing $\alpha,\beta,\gamma,\delta$, we can replace $x_i$ by $x_i - tx_j$ for any $j>i$, any $t\in\mathbb{R}$. Thus we can suppose that \begin{equation} \langle y_i,y_j \rangle = 0 \;, \end{equation} for any $i \neq j$. Since $A,B,C$ are homogenious functions of $y_{n-r+1},\cdots,y_n$, we can suppose that $\lVert y_i \rVert = 1$.

With the above assumptions, we have \begin{align} & {\lVert \alpha \rVert}_{\Lambda^{r-1} V}^2 = 1 \;,\nonumber\\ & {\lVert \beta \rVert}_{\Lambda^{r-2} V}^2 = \sum_{l=n-r+2}^n X_{l,n}^2 \;,\nonumber\\ & {\lVert \gamma \rVert}_{\Lambda^{r} V}^2 = 1 \;,\nonumber\\ & {\lVert \delta \rVert}_{\Lambda^{r-1} V}^2 = \sum_{l=n-r+1}^n X_{l,n}^2 \;,\nonumber\\ & {\langle \alpha , \delta \rangle}_{\Lambda^{r-1} V}^2 = X_{n-r+1,n}^2 \;. \end{align} Hence $A = B + C$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.